Long-range radio and Internet of things-inspired smart road reflectors for smart highways - Singh, Rajesh; Gehlot, Anita; Akram, Shaik Vaseem; Singh, Vivek Kumar; Iqbal, Mohammed Ismail; Mahala, Rahul (Institute of Advanced Engineering and Science, 2025)
The Internet of things (IoT) has been proven as an efficient technology for real-time monitoring of physical things through the Internet from any location. With the advancement in sensors and communication technologies, the implementation of IoT is adopted in wide extensions. Road reflectors on highway roads need to be automated and also powered with intelligence. With this motivation, we have proposed and implemented IoT and long range (LoRa) based architecture for the realization of smart road reflectors on the highway. To realize the proposed architecture, the hardware of the smart reflector and gateway is implemented on the university campus. During our implementation of the hardware, we observed the light intensity values that are sensed by smart reflectors on the server through LoRa and internet connectivity. In the future, we will be integrating additional sensors and also power the smart reflector with artificial intelligence to predict the fog status of a particular road.